PERBANDINGAN HUKUM PENGATURAN MEREK NON-TRADISIONAL ANTARA INDONESIA DENGAN SINGAPURA - Gultom, Eva Veronica; Kerti, N.G.N Renti Maharaini (Tribuere, 2023)
In the era of world trade, product needs are increasing day by day, the higher the trade competition, each company will improve the quality of the products they have. One of the developments in the field of trademarks is the emergence of protection against non-traditional forms of trademarks. The subject matter to be raised in this study regarding the similarities and differences in the regulation of non-traditional trademarks between Indonesia and Singapore. The writing of this thesis uses normative research type with comparative law research method. The data used are secondary data and primary data and drawing conclusions using the deductive method. This research is analyzed qualitatively. From the results of the research conducted, it can be concluded that the difference in non-traditional trademark arrangements between Indonesia and Singapore is that in Indonesia there are three forms of non-traditional trademarks, namely: three-dimensional brands, sound and holograms, while in Singapore there are seven forms of non-traditional brands, namely: three-dimensional marks, packaging aspects, sound, color, holograms, aroma, and motion. The similarity of non-traditional trademark arrangements with Indonesia is found in the trademark protection period which equally protects the trademark for up to 10 years from the date of receipt of the application.